TANGGUNG JAWAB PELAYANAN JASA PENGANGKUT TERHADAP KONSUMEN DALAM TRANSAKSI JUAL BELI ONLINE - Silvianingrum Aisyah Nurcahyani Latief (2023)
In accordance with the rapid development of technology, the development of the world of commerce is also increasing rapidly. In this case, it certainly makes it easier for consumers and business actors. Based on Law Number 8 of 1999 concerning Consumer Protection, it regulates the form of responsibility of business actors in the system of buying and selling agreements with consumers. In accordance with Article 24 which reads "business actors who sell goods and/or services to other business actors are responsible for claims and/or compensation", in a sale and purchase transaction they are not aware of any changes to goods or services made by business actors that are or are not in accordance with sample, quality, and composition. In accordance with current technological developments, it can make it easier for people to carry out activities, including buying and selling. Because the process of buying and selling can be done through internet media which is known as e-commerce. In carrying out transportation, there is an obligation, namely to organize transportation and maintain the safety of goods starting from receipt from the sender until they are handed over to the recipient. In this obligation, the carrier's responsibility arises as stipulated in Article 1239 of the Civil Code which stipulates that each person to do something or not to do something, if the debtor does not fulfill his obligations, obtains a settlement of the obligation by providing reimbursement of costs, losses and interest. So if in not carrying out its obligations, the responsibility of the carrier is to pay compensation.